Millennials' environmental awareness, price sensitivity and willingness to pay for green hotels / Joo-Ee Gan and Seo Nuli - Joo-Ee, Gan; Seo, Nuli (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2018)
This study analyse the Malaysian millennials' willingness to pay for green hotels. Through a survey with millennials as market segment, the exploratory study sought to examine the respondents' level of environmental awareness and price sensitivity. The findings suggest that environmental awareness was an important influencing factor in a respondent's willingness to pay for green hotels. However, the Malaysian millennials' demand for green hotel must be put in the context of their relatively low environmental awareness. Approximately half of the respondents were neither certain about the attributes of a green hotel, nor aware of green certification of hotels. Further, many respondents could not differentiate between a green hotel and a non-green hotel and could not be certain if the hotels they stayed in were green hotels. Moreover, price sensitivity was a major determinant for the purchase of green hotel where Malaysian millennials were concerned. The main implication of the study is managerial, in that the findings facilitate effective pricing, which is an essential aspect of a green hotel's marketing strategy.